Orchids inventory in Sintang Regency, West Kalimantan - ESTI ENDAH ARIYANTI; PA’I PA’I (Society for Indonesian Biodiversity, 2008)
Orchid is one of ornamental plants which have commercial value. Therefore most species are becoming threatened or even endangered because of over exploitation. In addition, its natural habitat is also decreasing. Conservation must be done urgently, both by in situ and ex situ conservation, which can be started by orchid inventory. The orchid inventory was done in TWA Bukit Kelam, TWA Baning and several places in Regency of Sintang, West Kalimantan. The result showed that there were 40 species belonged to 27 genera, which 32 species of them (20 genera) were epiphytic orchids and 8 species (7 genera) were terrestrial orchids.© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: inventory, orchid, Sintang, West Kalimantan